ЖАҢА МЕДИАДА ПУҚАРАЛЫҚ ЖУРНАЛИСТИКАНЫҢ СОЦИАЛЛЫҚ МАШҚАЛАЛАРДЫ ШЕШИЎДЕГИ МҮМКИНШИЛИКЛЕРИ - Есемуратова, С.А. (FAN va JAMIYAT, 2019)
The article discusses the important social problems of civil journalists and bloggers of the Republic of Karakalpakstan. There have been stated the points of view of scientists according to this issue on the example of citizen journalists.